2020
DOI: 10.1016/j.biopsych.2019.12.025
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Perampanel Rescues Cortical Gamma Dysregulation Associated With Parvalbumin Interneuron GluA2 Upregulation in Epileptic Syngap1+/− Mice

Abstract: BACKGROUND: Loss-of-function SYNGAP1 mutations cause a neurodevelopmental disorder characterized by intellectual disability and epilepsy. SYNGAP1 is a Ras GTPase-activating protein that underlies the formation and experience-dependent regulation of postsynaptic densities. The mechanisms that contribute to this proposed monogenic cause of intellectual disability and epilepsy remain unresolved. METHODS: We established the phenotype of the epileptogenesis in a Syngap1 1/2 mouse model using 24-hour video electroen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(59 citation statements)
references
References 74 publications
2
51
0
Order By: Relevance
“…Of note, while our manuscript was under review, locomotor video tracking data from Sullivan et al. (2020) reported a similar increase in nigh time motor activity in Syngap1 +/− mice compared to WT animals. Interestingly, our studies show that this same hyperactive phenotype was also observed in LL conditions—wherein Syngap1 +/− mice displayed increased overall activity relative to their WT littermates.…”
Section: Discussionmentioning
confidence: 53%
“…Of note, while our manuscript was under review, locomotor video tracking data from Sullivan et al. (2020) reported a similar increase in nigh time motor activity in Syngap1 +/− mice compared to WT animals. Interestingly, our studies show that this same hyperactive phenotype was also observed in LL conditions—wherein Syngap1 +/− mice displayed increased overall activity relative to their WT littermates.…”
Section: Discussionmentioning
confidence: 53%
“…Additionally, the detrimental effects of prolonged sleep deprivation on cognitive performance are also well established [37][38][39][40] . Our previous study established significant disruption of cortical gamma homeostasis in adult Het +/mice 15 . The identification of normal slow wave sleep compensation to the increased sleep pressure in both WT +/+ and Het +/pups highlight the uniqueness of the qEEG biomarker related to gamma homeostasis which is known to depend on function of fast-spiking PV interneurons 41,42 .…”
Section: Increasing Sleep Pressure Further Aggravates Abnormal Corticmentioning
confidence: 95%
“…All surgical procedures and perampanel (PMP) dosing implemented in this study were as previously published 15 . At P18 subdural EEG and suprascapular EMG electrode implantation was performed under isoflurane anesthesia (4%–1.5%).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations